Konsep Keserasian Gender sebagai Respons Wacana Kesetaraan Gender dalam Al Qur’an (Telaah Tafsir al-Mishbah Q.S An- Nisa’: 34) - Ana Miftahul Hidayah; Abdul Kadir Riyadi (Universitas Darussalam Gontor, 2023)
Gender equality is a Western concept that is well applied in its culture to humanize women, for the dark history experienced by women during the middle ages which had an impact on traumatic attitudes towards men and religious statements, and with this sensitive nature, feminist groups oppose statements that are valued gender bias, especially in the holy texts, by adhering to the concept of 'gender equality' which means equal as a whole. However, the results of applying the concept of gender equality to the Qur'an state that the statement of the Qur'an and the interpretation of previous scholars' values ​​is gender bias, especially in Q.S An Nisa': 34 regarding male leadership in the household, which is then responded by many Muslim leaders and even contemporary mufassir, one of them with the 'concept of gender harmony'. Therefore, this research will discuss how the application of the concept of gender equality to Q.S An Nisa': 34 and the response of Muslim leaders and commentators do they agree with 'gender equality', or are they against it? To answer this question, this research used a descriptive method. analysis related to the interpretation of Quraish Shihab who is a contemporary mufassir and critical thinker, thus in this study the results were obtained that in relations between men and women cannot be equalized as a whole as the concept of 'gender equality', because both have differences in nature which turns out to have been adjusted with their respective tasks such as discussing the concept of 'gender harmony'